Semantic mining and web service discovery techniques for media resources management. (24th January 2006) - Sakkopoulos, Evangelos; Kanellopoulos, Dimitris; Tsakalidis, Athanasios
The proposed techniques facilitate semantic discovery and interoperability of web services that manage and deliver web media content. As a test-bed, a web management system is discussed that provides vocational monographs for occupational guidance. The key idea of the proposed web service based architecture is that the WS of participating members share their vocational monographs and related resources, resulting in the overall system capacity increase. Mechanisms and techniques are presented concerning: an 'information desk', which provides an adaptive search user interface; discovery functions based on semantic representation of the WS' monographs; mining into monographs based on their semantic representation; a metric-based evaluation model for the web monographs; dynamic ranking of retrieved content list; consumption mechanisms for the career counsellors' local WS; e-payment; universal usability access. This analysis can be exploited in the practice of a new Occupational Guidance Policy.